The Don Giovanni moment : essays on the legacy of an opera - Goehr, Lydia; Herwitz, Daniel Alan, 1955- (Columbia themes in philosophy, social criticism, and the arts., 2006)
Mozart's Don Giovanni is an operatic masterpiece full of iconic and mythical tensions that still resonate today. The work redefines the terms of power, seduction, and morality, and the resulting conflict between the aesthetic and the ethical is deeply rooted in the Enlightenment and romanticism. The Don Giovanni Moment is the first book to examine the aesthetic and moral legacy of Mozart's opera in the literature, philosophy, and culture of the nineteenth century.